2019
DOI: 10.1055/s-0039-3400251
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Kisspeptin Neurons Coordinate Reproductive Activities with Metabolism

Abstract: Hypothalamic control of fertility is the quintessential homeostatic function. However, fertility is metabolically demanding; so, there must be coordination between energy states and reproductive functions. Because gonadotropin-releasing hormone (GnRH) neurons are devoid of many of the critical metabolic hormone receptors for sensing nutrient levels, it has long been recognized that the sensing of energy stores had to be done by neurons presynaptic to GnRH neurons. Some of the obvious players have been the anor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 96 publications
(153 reference statements)
1
34
0
1
Order By: Relevance
“…The tyrosine phosphatase through its dephosphorylation of STAT3 inhibits downstream signaling of leptin and insulin in POMC neurons (Dodd Garron T. et al, 2018). Moreover, Kiss1 ARH neurons are an integral part of an anorexigenic circuit in the hypothalamus (Navarro Víctor M., 2020; Qiu J., Rivera, et al, 2018; Rønnekleiv et al, 2019) and may provide the excitatory glutamatergic drive to the paraventricular hypothalamus to generate rapid satiety following a meal (Fenselau et al, 2017). However, future experiments will need to test this directly by using ChR2-assisted circuit mapping along with high frequency stimulation of Kiss1 ARH neurons to further document this pathway (Qiu J., Rivera, et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tyrosine phosphatase through its dephosphorylation of STAT3 inhibits downstream signaling of leptin and insulin in POMC neurons (Dodd Garron T. et al, 2018). Moreover, Kiss1 ARH neurons are an integral part of an anorexigenic circuit in the hypothalamus (Navarro Víctor M., 2020; Qiu J., Rivera, et al, 2018; Rønnekleiv et al, 2019) and may provide the excitatory glutamatergic drive to the paraventricular hypothalamus to generate rapid satiety following a meal (Fenselau et al, 2017). However, future experiments will need to test this directly by using ChR2-assisted circuit mapping along with high frequency stimulation of Kiss1 ARH neurons to further document this pathway (Qiu J., Rivera, et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there is compelling evidence that Kiss1 ARH neurons are the critical “command” neuron for coordinating energy states with reproductive functions (see (Navarro Víctor M., 2020; Rønnekleiv et al, 2019) for review). Insulin may be the critical metabolic hormone providing feedback since neuron-specific deletion of insulin receptors causes hypothalamic hypogonadism and infertility (Bruning et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in vitro mice study discovered that insulin can directly modulate GnRH neurons, in vivo studies of adult ewes and mice gave an opposite evidence [ 29 , 30 ]. Indeed, insulin activates Kiss1 ARC in mice via functional insulin receptors [ 31 ]. Also, in laboratory animals, insulin excites ARC POMC neurons and suppresses NPY/AgRP neurons [ 30 ].…”
Section: The Roles Of Cr In Hpo Axismentioning
confidence: 99%
“…Interestingly, CR enhances the negative feedback (mice) [ 2 , 36 ] and attenuates the positive feedback (rhesus monkeys) [ 46 ] of E 2 on HPO axis. It is also found that E 2 as an anorexigenic factor enables to inhibit ARC NPY/AgRP neurons and activate ARC POMC neurons [ 31 ]. Therefore, low E 2 level caused by CR also contributes to the inhibition of HPO axis.…”
Section: The Roles Of Cr In Hpo Axismentioning
confidence: 99%